TEL-AML-1 fusion gene in children with acute lymphoblastic in basra pediatric oncology center - G. Hassan, J. (Scientific Journal of Medical Science, 2014)
TEL-AML-1 fusion gene resulting from 12,21 chromosomal translocation is believed to be the most common molecular genetic abnormality in childhood acute lymphoblastic leukemia(ALL). This study has been conducted to investigate the frequency of this fusion gene in children suffering from ALL attending the oncology unit in Basra hospital for pediatric and gynecology during the period from May 2009 to April 2010, and point out the different laboratory features associated with this anomalies. A total of 120 blood samples were collected( 60 early diagnosed all children and 60 healthy children as control group). The controls were matched with cases by age and sex. Ribonucleic acid (RNA) has been successfully extracted from 40 ALL cases fresh blood used for the detection of TEL-AML-1 fusion gene by reverse transcriptase- polymerase chain reaction (RTPCR). Of newly diagnosed all cases 27.5% were positive for TEL-AML- 1 fusion gene as well as 5% among the control group. All TEL-AML-1 positive cases showed an age peak between 3-6 years and tend to occur more frequent among female than males. TEL-AML-1 positive cases that classified as standard risk group were accounted for 72.3% while 27.3% were high risk group (P<0.05) and according to the French- -American-British (FAB) classification criteria, 72.3% of high risk and 68% of standard risk groups belong to L2 stage. TEL-AML-1 fusion gene identifies a subset of pediatric ALL associated with a number of laboratory markers of good prognosis and should thus be considered in routine molecular work of ALL to confirm its impact on clinical outcome and to design suitable therapy.